Genetic association and functional characterization of MCPH1 gene variation in bipolar disorder and schizophrenia. Issue 4 (11th March 2019) - Al Eissa, Mariam M.; Sharp, Sally I.; O'Brien, Niamh L.; Fiorentino, Alessia; Bass, Nicholas J.; Curtis, David; McQuillin, Andrew
Abstract: A rare microcephalin 1 gene ( MCPH1 ) variant rs61749465A>G (p.Asp61Gly) with prior evidence for association with schizophrenia ( p = 3.78 × 10 −7 ) was tested for association in 2, 300 bipolar disorder (BPD) participants, 1, 930 SCZ participants and 1, 820 normal comparison subjects. We report evidence for association of rs61749465A>G with BPD ( p = 0.0009). rs61749465 is located in the N‐terminal of the BRCT1 domain of MCPH1. Bioinformatic analysis predicted the Asp61Gly substitution to be damaging to MCPH1 function. A second MCPH1 BRCT1 domain variant (rs199422124C>G; p.Thr27Arg), reported to cause autosomal recessive microcephaly, was not detected in the participants tested here. We sought to characterize the functional effects of these variants on MCPH1 function. Cell count assays indicated that rs199422124 allele G had a greater impact on cell survival compared to the G allele of rs61749465. Gene expression analysis combined with gene network and pathway analysis indicated that rs61749465 allele G may impact protein translation and cell cycle control. The evidence for association between rs61749465A>G and psychosis in both BPD and SCZ warrants further replication. Likewise, the data from the functional analyses point to molecular mechanisms that may underlie the proposed MCPH1 mediated risk of psychosis and pathogenesis in autosomal recessive microcephaly require additional experimental validation.